Effect of Cistanche deserticola Polysaccharides on the Treatment of Ulcerative Colitis in Mice by Regulating Coke Death Through NLRP3/GSDMD Signaling Pathway - Guangli MA; Qing LI (Shipin gongye ke-ji)
This study aims to investigate the therapeutic effects and mechanisms of Cistanche deserticola polysaccharides (CDPS) on dextran sulphate sodium (DSS)-induced ulcerative colitis (UC) in mice. Mice were randomly divided into normal group, model group, high and low dose CDPS groups, and positive control sulfasalazine group. Except for the normal group, other groups freely consumed 3.5% DSS solution while receiving corresponding drug treatments via gavage. After treatment, general conditions of mice were recorded. Colonic tissue pathological changes were observed. ELISA was used to detect inflammatory factors and mediators in serum and colonic tissue. qPCR measured mRNA expression levels of inflammatory factors and pyroptosis pathway-related proteins in colonic tissue. Immunohistochemistry and immunofluorescence analyzed ZO-1 and Occludin protein expression levels, degree of apoptosis, and pyroptosis pathway protein expression in mouse colonic tissue. Results showed that compared with the model group, both high and low dose CDPS groups significantly improved DSS-induced general conditions and colonic pathological status, reducing pathological scores (by 64.43% and 48.50% respectively, P<0.01). High and low dose CDPS groups significantly reduced levels of TNF-α, IL-1β, IL-6, and IFN-γ (P<0.01 or P<0.05) in serum and colonic tissue, while increasing IL-10 levels (P<0.01 or P<0.05). Additionally, both CDPS doses significantly inhibited iNOS and COX-2 expression in colonic tissue (P<0.01 or P<0.05). Immunohistochemistry and immunofluorescence results showed that CDPS groups inhibited NLRP3, Caspase-1, and GSDMD-N expression, thereby reducing cell pyroptosis. qPCR analysis confirmed that CDPS groups downregulated mRNA expression of IL-1β, IL-6, TNF-α, NLRP3, Caspase-1 and GSDMD, indicating that CDPS had significant therapeutic effects on DSS-induced ulcerative colitis in mice, with mechanisms potentially related to inhibiting inflammatory response, improving intestinal barrier function, and reducing cell apoptosis and pyroptosis.